Analisis Pembentukan Badan Usaha Milik Desa (BumDesa) Di Kabupaten Luwu Timur - Sitti Maryam Bahri (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This study aims to determine the opportunities for the establishment of BUM Desa and the role or business of the Regional Government in the formation (BUM Desa) in East Luwu regency. To achieve these objectives used qualitative research methods by parsing data descriptively. Data collection technique is done by observation, interview, and document and archive by using qualitative descriptive analysis technique. This research aim to know the opportunity of BUM Desa formation and also role or effort of Local Government in establishment (BUM Desa) in East Luwu Regency. To achieve these objectives used qualitative research methods by parsing data descriptively. Data collection technique is done by observation, interview, and document and archive by using qualitative descriptive analysis technique. The results showed: First, from two villages sampled Bangun Jaya Village and Tarengge Village have Factors which become an opportunity to encourage the establishment of BUM Desa, but in its implementation still not run effectively because of lack of knowledge, creativity and innovation of society and government The village in developing the potential and scientifically deepening analysis of potential opportunities in each village has not been undertaken by the local government of East Luwu regency, while the analysis for the establishment is submitted to each village. Secondly, based on the Law underpinned by the Regional Regulation, the East Luwu District Government requires the Village to establish and establish the Village.